1994
DOI: 10.1038/370068a0
|View full text |Cite|
|
Sign up to set email alerts
|

Parthenogenetic activation of oocytes in c-mos-deficient mice

Abstract: In Xenopus the c-mos proto-oncogene product (Mos) is essential for the initiation of oocyte maturation, for the progression from meiosis I to meiosis II and for the second meiotic metaphase arrest, acting as an essential component of the cytostatic factor CSF. Its function in mouse oocytes is unclear, however, as is the biological significance of c-mos mRNA expression in testes and several somatic tissues. We have generated c-mos-deficient mice by gene targeting in embryonic stem cells. These mice grew at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
270
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(284 citation statements)
references
References 20 publications
11
270
0
3
Order By: Relevance
“…The Mos pathway in mouse, however, does not precisely parallel that in Xenopus. Oocytes from Mos knockout mice arrest properly at metaphase of meiosis II (Hashimoto et al, 1994), but then spontaneously exit meiosis after 2-4 hr (Verlhac et al, 1996;Colledge et al, 2004). Therefore, Mos is necessary to maintain, but not establish, meiotic arrest in mouse.…”
Section: Meiosis Arrest and Release In Vertebratesmentioning
confidence: 99%
“…The Mos pathway in mouse, however, does not precisely parallel that in Xenopus. Oocytes from Mos knockout mice arrest properly at metaphase of meiosis II (Hashimoto et al, 1994), but then spontaneously exit meiosis after 2-4 hr (Verlhac et al, 1996;Colledge et al, 2004). Therefore, Mos is necessary to maintain, but not establish, meiotic arrest in mouse.…”
Section: Meiosis Arrest and Release In Vertebratesmentioning
confidence: 99%
“…Our previous study [11] showed that MAP kinase might be involved in microtubule nucleation by -tubulin in pig oocytes. However, it was reported that mouse oocytes deficient in MAP kinase activity could still divide and release polar bodies [6,[12][13][14]. Until now, the targets of MAP kinase in the meiotic spindle remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the MII arrest is maintained by cytostatic factor (CSF) activity, with MOS/MEK/ERK cascade being its essential components [4,10,12,13,15]. Although existing evidence has suggested that MAP kinase is important for metaphase arrest, almost all data come from mos -/-oocytes or other models indication MAP kinase is not activated during the entire maturation process.…”
Section: Introductionmentioning
confidence: 99%
“…In mos-deficient mice or in mouse oocytes injected with mos double-stranded RNA, approximately 60 -75% of oocytes fail to arrest at metaphase II and undergo parthenogenetic activation (Choi et al, 1996;Colledge et al, 1994;Hashimoto et al, 1994;Wianny and Zernicka-Goetz, 2000). In this study, microinjection of 340 pg of mos MO, 17 pg of mos MO, or 340 pg of control MO into the cytoplasm of germinal vesicle stage mouse oocytes resulted in respective parthenogenetic activation rates of 56, 23, and 0% when scored 20 h after 3-isobutyl-1-methyl-xanthine (IBMX) removal (Fig.…”
mentioning
confidence: 99%